silahkan yg mau itut ._.
f(x) = 6x + x³ - 8(9) + x
f(2) =
f(x) = 6x + x³ - 8(9) + x
f(2) =
![](https://id-static.z-dn.net/files/d08/c5204e29fb4b88766ce59043939e4ffd.jpg)
Penjelasan dengan langkah-langkah:
f(x) = 6x + x³ - 8(9) + x
f(2) = 6(2) + 2³ - 8(9) + 2
f(2) = ( 6 × 2 ) + ( 2 × 2 × 2 ) - ( 8 × 9 ) + 2
f(2) = 12 + 8 - 72 + 2
f(2) = 20 - 72 + 2
f(2) = -52 + 2
f(2) = -50
pertanyaan :
f(x) = 6x + x^3 - 8(9) + x
f(2) = ...
jawaban :
f(x) = 6x + x^3 - 8(9) + x
f(2) = 6(2) + 2^3 - 8(9) + 2
f(2) = 12 + (2 × 2 × 2) - 72 + 2
f(2) = 12 + (4 × 2) - 72 + 2
f(2) = 12 + 8 - 72 + 2
f(2) = 20 - 72 + 2
f(2) = (-52) + 2
f(2) = (- 50)
》Mellvina02《
[answer.2.content]